2020
DOI: 10.1117/1.nph.7.2.020901
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of combined functional near-infrared spectroscopy and transcranial direct-current stimulation studies

Abstract: Significance: Combining transcranial direct-current stimulation (tDCS) with functional nearinfrared spectroscopy (fNIRS) is a recent approach to exploring brain activation evoked by neurostimulation. Aim: To critically evaluate studies combining tDCS and fNIRS and provide a consolidated overview of cortical hemodynamic responses to neurostimulation. Approach: Key terms were searched in three databases (MEDLINE, EMBASE, and PsycINFO) with cross-referencing and works from Google Scholar also evaluated. All studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 92 publications
(237 reference statements)
1
14
0
Order By: Relevance
“…Moreover, compared to fMRI, fNIRS is both portable and less sensitive to motion artifacts. As a useful neuroimaging tool, fNIRS is widely used to investigate the high-level cerebral cortex's hemodynamic activities and the related functional network in various neuromodulation studies, such as TMS (Park et al, 2017;Curtin et al, 2019b), tES (Patel et al, 2020), and acupuncture (Takamoto et al, 2010;Ghafoor et al, 2019;Rojas et al, 2019). Previous acupuncture studies also showed the prospect of applying fNIRS to study acupuncture's neural mechanism (Takamoto et al, 2010;Ghafoor et al, 2019;Rojas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared to fMRI, fNIRS is both portable and less sensitive to motion artifacts. As a useful neuroimaging tool, fNIRS is widely used to investigate the high-level cerebral cortex's hemodynamic activities and the related functional network in various neuromodulation studies, such as TMS (Park et al, 2017;Curtin et al, 2019b), tES (Patel et al, 2020), and acupuncture (Takamoto et al, 2010;Ghafoor et al, 2019;Rojas et al, 2019). Previous acupuncture studies also showed the prospect of applying fNIRS to study acupuncture's neural mechanism (Takamoto et al, 2010;Ghafoor et al, 2019;Rojas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the interaction between tDCS induced effects on cognition and cerebral perfusion across aging remains widely unknown. Post-tDCS cerebral perfusion changes have been measured using neuroimaging techniques such as functional magnetic resonance imaging (fMRI) (Antal et al, 2011 ) and functional near-infrared spectroscopy (fNIRS) (Patel et al, 2020 ). Widespread decreases in cerebral perfusion after cathodal and anodal tDCS have been reported using arterial spin labeling (Stagg et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, regional decreases in blood-oxygen-level-dependent signals have been reported beyond, but not within, the region of stimulation (Antal et al, 2011 ). Regarding fNIRS, significant interindividual and methodological variability on reported tDCS effects exists in tDCS-fNIRS study designs (Patel et al, 2020 ). However, increases in cortical activation are reported during resting state; interestingly, a decreased level of cortical activation has also been reported during online tasks (Patel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, fNIRS has been used to investigate pain perception and its therapeutic interventions, as well as to measure the effect of tDCS on cortical activation. [21][22][23][24] Recently, we explored the longitudinal effect of tDCS on the hemodynamic response to thermal pain in knee OA patients using fNIRS 25 and found that cortical activity increased over time. However, to our knowledge, no study has yet investigated the neuromodulatory effect of a combination of tDCS and MBM on the same population.…”
Section: Introductionmentioning
confidence: 99%